Analisis Implementasi Model Kooperatif Tipe STAD dalam Pembelajaran IPAS untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Rahmadhani, Setiyawati; Indrapangastuti, Dewi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Education is a crucial element in developing human resources; however, IPAS (Science and Social Studies) learning in elementary schools often faces challenges, such as limited instructional innovation and low student concentration. The cooperative learning model Student Team Achievement Division (STAD) offers a promising alternative as it promotes collaboration, creativity, and critical thinking. This study aims to analyze the implementation of the STAD model in IPAS learning through a literature review. A total of 20 sources published between 2020 and 2025 were systematically analyzed. The findings indicate that the STAD model is effective in improving students’ learning outcomes, motivation, attitudes, and knowledge, while also significantly enhancing students’ skills such as communication, collaboration, and independence. Moreover, the model contributes to creating an active, interactive, and enjoyable learning environment. The implementation of the STAD cooperative learning model in IPAS education at the elementary school level shows a significant improvement in various aspects of student learning outcomes. It is recommended that this research be continued by examining the factors that influence the successful implementation of the STAD model in a broader context.Pendidikan adalah elemen krusial untuk mengembangkan sumber daya manusia, namun pembelajaran IPAS di Sekolah Dasar kerap menghadapi tantangan, seperti rendahnya inovasi pembelajaran dan kurangnya konsentrasi siswa. Model pembelajaran kooperatif tipe Student Team Achievement Division (STAD) menjadi alternatif yang potensial karena mendorong kerja sama, kreativitas, serta kemampuan berpikir kritis. Penelitian ini bertujuan untuk menganalisis implementasi model STAD dalam pembelajaran IPAS melalui studi literatur. Sebanyak 20 literatur dari tahun 2020–2025 dianalisis menggunakan pendekatan sistematis. Hasil kajian menunjukkan bahwa model STAD efektif dalam meningkatkan hasil belajar, motivasi, sikap, pengetahuan, serta secara signifikan mengembangkan keterampilan siswa seperti komunikasi, kolaborasi, dan kemandirian. Selain itu, model ini turut membentuk lingkungan belajar yang aktif, interaktif, dan menyenangkan. Penerapan model pembelajaran kooperatif tipe STAD dalam pembelajaran IPAS di Sekolah Dasar menunjukkan peningkatan yang signifikan dalam berbagai aspek hasil belajar siswa. Disarankan agar penelitian ini dapat dilanjutkan dengan mengkaji faktor-faktor yang mempengaruhi keberhasilan implementasi model STAD dalam konteks yang lebih luas.